Temperature and soil nutrients drive the spatial distributions of soil macroinvertebrates on the eastern Tibetan Plateau. Issue 3 (5th March 2020) - Yang, Yulian; Wu, Qinggui; Yang, Wanqin; Wu, Fuzhong; Zhang, Li; Xu, Zhenfeng; Liu, Yang; Tan, Bo; Li, Han; Zhou, Wei
Abstract: Improved knowledge of biological diversity patterns associated with elevation and their driving factors is indispensable for developing ecological theories. However, the results for the elevational distribution patterns of soil fauna are not consistent due to differing climates and vegetation. Here, we present a comprehensive analysis of soil macroinvertebrate composition and structure among different forests at three elevations on the eastern Tibetan Plateau, China. A total of 16, 559 individuals belonging to 24 orders and 100 families were collected, and the macroinvertebrate individual abundance, family richness, and diversity apparently increased with increasing elevation. Moreover, remarkable seasonal dynamics were observed for both the composition and functional structure of soil macroinvertebrates among forest types and were inconsistently affected by different environmental factors. The structural equation model suggested that elevation indirectly affected soil macroinvertebrate abundance by modulating climate (e.g., temperature) and soil quality (e.g., soil organic carbon and total nitrogen). Additionally, although vegetation had minor direct effects on soil macroinvertebrate abundance, it might indirectly influence soil macroinvertebrate abundance by regulating plant litter input. Our results indicate that temperature and soil nutrients are critical factors of soil macroinvertebrate elevational distributions and highlight the importance of plant litter input in determining the composition and structure of soil macroinvertebrates at different elevations.